KEMAMPUAN TEKNIK DASAR FOREHAND DAN BACKHAND PADA PEMAIN BAVETI BANJARBARU - Selma Alifah Anggraeni; Lazuardy Akbar Fauzan; Edwin Wahyu Dirgantoro (Universitas Negeri Medan, 2025)
The purpose of this study is to find out how the basic technique of forehand and backhand in the sport of court tennis played by the Indonesian Tennis Veteran Athlete Ranks (BAVETI). The methodology of this research is quantitative descriptive, and a measurement test was carried out to obtain data. The Hewitt Achievement Test is the instrument used in this study. The subjects in this study were 18 people from the BAVETI club in Banjarbaru. The results of this study categorized forehand ability as; 0 samples (0%) were very poor, 6 samples (33%) were poor, 8 samples (44%) were moderate, 3 samples (17%) were good and 1 sample (6%) was very good. Categorizing backhand ability at; 1 sample (6%) is very poor, 4 samples (22%) are poor, 7 samples (39%) are moderate, 6 samples (33%) are good and 0 samples (0%) are very good. The conclusion of this study is that the basic forehand and backhand technique skills of BAVETI Banjarbaru city are in the